(untitled) (Research, Society and Development, 2021)
The discourse and practice of incorporating diversity into organizations do not always reconcile respect for difference with equal opportunities. Therefore, this article aims to analyze practices and discourses regarding the management of diversity in the largest organizations in Ijuí/RS, “the Land of Diversified Cultures”. It is a case study, operationalized based on quantitative and qualitative methods. First, the questionnaire of the “Social, Racial and Gender Profile of the 500 Largest Companies in Brazil” was applied to the 20 largest companies in Ijuí, prepared by the Ethos Institute. This instrument, which has already been validated in previous research, seeks to assess how organizations are dealing with diversity management within the scope of their internal policies. Then, 37 interviews were carried out with managers and representatives of other employees. The latter were divided into: minorities, representing the groups that constitute the diversity under study (Pcds, blacks, women and people over 45) and non-minorities, representing the other employees. The survey revealed that organizations do not invest in diversity policies. Some managers interviewed recognize that organizations have sought to include people with different profiles, however, they recognize that the validity of this action is threatened when individuals do not credit diversity and when there is a lack of opportunities for advancement and recognition. In the perception of minorities, organizations do not have an inclusive culture that allows for belonging practices. The transformation of this agenda requires the breaking of prejudiced and discriminatory attitudes in the corporate environment.